THE COMPARISON OF ISLAMIC EDUCATION LEARNING OUTCOME WHICH WAS TREATMENT BY USING COOPERATIVE LEARNING MODEL OF STAD TYPE AND NHT TYPE AT STUDENTS ClASS X SMA PALOPO 3 - Sangjaya, Chandra; Muzakkir, Muzakkir; Rapi, Muh. (Jurnal Diskursus Islam, 2020)
This research discussed about the comparison of learning outcomes in Islamic Education students who used the STAD type cooperative learning model and NHT type class X SMA Negeri 3 Palopo. This reasearch aimed to: 1) to determine the learning outcomes of Islamic Education students taught using the STAD type cooperative model in class X SMA Negeri 3 Palopo, 2) to know the Islamic Education learning outcomes of students taught using the NHT cooperative model on class X SMA Negeri 3 Palopo, 3) to Analyze the differences in Islamic Education learning outcomes of students taught by the STAD type cooperative model and student learning outcomes taught by the NHT cooperative model in Class X SMA Negeri 3 Palopo. This research was a quantitative research with a non-equivalent control group design. The population was all students of class X SMA Negeri 3 Palopo, totaling 260 students. The technique sampling was done by using purposive sampling. The instrument used was a test with descriptive statistical analysis and inferential analysis. Based on the analysis of descriptive data for the learning outcomes of students taught by using the STAD type cooperative learning model is very good category. The learning outcomes of students taught by using NHT type of cooperative learning model are very good category. Based on inferential analysis obtained a significant value> α (0.716> 0.05) then, it can be said that there is no significant difference between the learning outcomes of Islamic Religious Education taught using the STAD type cooperative learning model and those taught using the NHT learning model in Class students X SMA Negeri 3 Palopo.